2014
DOI: 10.1590/1807-7692bar2014130008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and Encouragement of Entrepreneurial Behavior: Antecedents Analysis from Managers' Perspectives

Abstract: One of the paths chosen by businesses to increase their competitiveness through innovation is by encouraging employees to adopt a more entrepreneurial attitude. Although studies on Entrepreneurial Orientation have brought important contributions, anecdotal evidences of entrepreneurial employees not affected by corporate initiatives drive attention to managers' roles in developing entrepreneurial behavior. We found good possible explanations in the theory Induced vs. Autonomous Entrepreneurial Behavior. Thus, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 22 publications
(42 reference statements)
2
15
0
1
Order By: Relevance
“…In addition, and attending to the identified gap (Escobar-Sierra, 2015; Escobar-Sierra and Vera-Acevedo, 2016), the results confirm the suspicions of other authors such as (1) Bedoya, Toro and Arango (2017), Corbett, et al (2013) and Hashimoto and Nassif (2014) when confirm the incidence of a leader's attitudes on the innovation strategy, in this case on the SRI. (2) Castrogiovanni, Urbano and Loras (2011) and Urbano, Toledano and Ribeiro-Soriano (2011) when relating the employees'attitudes with strategic organizational matters such as innovation.…”
Section: Discussion Of the Results Obtainedsupporting
confidence: 80%
See 2 more Smart Citations
“…In addition, and attending to the identified gap (Escobar-Sierra, 2015; Escobar-Sierra and Vera-Acevedo, 2016), the results confirm the suspicions of other authors such as (1) Bedoya, Toro and Arango (2017), Corbett, et al (2013) and Hashimoto and Nassif (2014) when confirm the incidence of a leader's attitudes on the innovation strategy, in this case on the SRI. (2) Castrogiovanni, Urbano and Loras (2011) and Urbano, Toledano and Ribeiro-Soriano (2011) when relating the employees'attitudes with strategic organizational matters such as innovation.…”
Section: Discussion Of the Results Obtainedsupporting
confidence: 80%
“…Furthermore, the one type of behavior includes (a) agreement between a leader's values and way of acting, and the three perceptions include (I) the leader's perception in terms of completion of the beginning tasks, (II) control of emotions and (III) interest in others. To finally, alert about how the results correspond with the previous recommendations of authors such as Castrogiovanni, Urbano andLoras (2011), Corbett, et al (2013), Hashimoto and Nassif (2014) and Lau, et al (2012), and with gap identified by Marinova and Phillimore (2003), in the last generation of innovation.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…These studies also considered measures such as time for learning, experimentation and reward for ideas and innovation. Hashimoto and Nassif (2014) claimed that entrepreneurial culture characteristics such as valuing employees, reward systems and time for learning induce entrepreneurial behaviour among employees. Ideas and innovation flourish within such an entrepreneurial culture.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, TMTs must cultivate a good relationship with team members in order to encourage them to generate ideas and identify opportunities. Secondly, TMTs must protect their entrepreneurs from punishment, should the latter's efforts fail, considering that employees with an autonomous entrepreneurial behavior already have an EO (Hashimoto & Nassif, 2014). …”
Section: Discussionmentioning
confidence: 99%